Efficacy and safety of desvenlafaxine in treating patients with major depressive disorder: a network meta-analysis - Li, Lingke; Ren, Xiaodan; Yuan, Chenzhao (Frontiers in Neuroscience, 2026)
Background and objectiveDesvenlafaxine (DVS), a commonly used serotonin-norepinephrine reuptake inhibitor (SNRI), is widely applied in the treatment of major depressive disorder (MDD). However, the efficacy and safety of different DVS dosages remain controversial. This study aims to systematically evaluate the efficacy and safety of various doses of DVS in treating MDD, providing evidence-based guidance for clinical dose selection.MethodsA systematic search was conducted in PubMed, Embase, Web of Science, and the Cochrane Library to identify randomized controlled trials (RCTs) comparing different doses of DVS in adult MDD patients. A Bayesian random-effects model was employed for network meta-analysis, and surface under the cumulative ranking curve (SUCRA) was used to assess the overall performance of each dose in terms of efficacy (HAM-D17, CGI-S, MADRS scores) and safety (treatment-emergent adverse events, TEAEs). Publication bias was assessed using funnel plots. All data analyses were performed using R Studio and STATA.ResultsA total of eight RCTs were included. The analysis showed that DVS at 50, 100, 200, and 400 mg/day significantly outperformed placebo in improving HAM-D17, CGI-S, and MADRS scores, with the 200 mg/day dose showing numerically greater improvement than the other doses. Regarding safety, there were no statistically significant differences in adverse event rates between any DVS dose and placebo (P > 0.05). According to the SUCRA rankings, DVS 200 mg/day tended to appear higher in the probabilistic ranking, although this reflects relative ordering rather than conclusive evidence of clinical superiority.ConclusionDVS at doses ≥ 50 mg/day significantly improves depressive symptoms compared with placebo. Among the evaluated doses, 200 mg/day consistently showed numerically greater improvements while maintaining acceptable tolerability; however, the certainty of dose differences remains limited, and no definitive “optimal” dose can be established based on the current evidence.